Green biologically synthesized metal nanoparticles: biological applications, optimizations and future prospects - Radwa N Morgan; Khaled M Aboshanab (Future Science OA, 2024)
In green biological synthesis, metal nanoparticles are produced by plants or microorganisms. Since it is ecologically friendly, economically viable and sustainable, this method is preferable to other traditional ones. For their continuous groundbreaking advancements and myriad physiochemical and biological benefits, nanotechnologies have influenced various aspects of scientific fields. Metal nanoparticles (MNPs) are the field anchor for their outstanding optical, electrical and chemical capabilities that outperform their regular-sized counterparts. This review discusses the most current biosynthesized metal nanoparticles synthesized by various organisms and their biological applications along with the key elements involved in MNP green synthesis. The review is displayed in a manner that will impart assertiveness, help the researchers to open questions, and highlight many points for conducting future research.